The Correlation of Immunohistochemical Expression of Matrix Metalloproteinase-9 with Tumor Budding Index and Histopathological Grading in Endometrial Carcinoma - Nafilah Yuzar, Devi; Chrestella, Jessy; Ibnu Alferraly, T.; Soekimin, Soekimin; Trisna Mariedina, Causa; Nadjib Dahlan Lubis, M. (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2025)
ABSTRACT Background Malignancies of the uterine corpus are the sixth most common malignancy in women, where endometrial carcinoma accounts for the largest number of these cases. Tumor budding has been described as a sign of cancer cell motility and as an early step in the metastatic process. One of the most important aspects of the metastatic process is the correlation between tumor budding and the epithelial mesenchymal transition (EMT), that are characterized by an increase matrix metalloproteinases. One of MMPs is Matrix Metalloproteinase-9 (MMP-9) which plays a role in degrading the extracellular matrix and basement membrane, which is a prerequisite for the process of invasion and metastasis. Method This is an analytic study with a cross sectional approach on 38 surgical samples diagnosed as endometrial carcinoma and then performed with MMP-9 immunohistochemical staining. The statistical analysis was performed to analyze the correlation of immunohistochemical expression of MMP-9 with tumor budding index and histopathological grading in endometrial carcinoma. Results Based on statistical analysis for 38 samples of endometrial carcinoma patients, there was a significant correlation between the immunohistochemical expression of MMP-9 with tumor budding index with p-value: 0.021 and histopathological grading with p-value: 0.005. Conclusion There was a significant correlation between the immunohistochemical expression of MMP-9 with tumor budding index and histopathological grading in endometrial carcinoma, where the immunohistochemical expression of MMP-9 increased at high tumor budding index and histopathological grading as well.